Influence of hot rolling on the interface microstructure and mechanical properties of explosive welded Mg/Al composite plates. Issue 4 (6th February 2017) - Wang, Dongya; Cao, Xiaoqing; Wang, Lifei; Cao, Miao; Wang, Wenxian
Abstract: Abstract : The influence of hot rolling on the evolution of the interface microstructure as well as mechanical properties of the Mg/Al explosive welding composite plates was investigated. The hardening phenomenon induced by explosive welding could be eliminated effectively through preheating treatment. An intermetallic compound layer consisting of Al3 Mg2 and Mg17 Al12 was observed at the Mg/Al interface after annealing at 400 °C. The composite plate then was hot rolled at 400 °C with different reduction ratios. The composite plates presented different degrees of warp and edge cracks with increasing the reduction ratio. At the reduction ratio of 30%, the coordination deformation ability of the constituent Mg and Al alloys is consistent with the composite plate. The results showed that the tensile strength and the elongation of the composite plates increased significantly after hot rolling owing to the dynamic recrystallization and the intermetallic compounds thickness decrease during hot rolling.